Potentiometric Studies of the pH Effect on the Coordination Behavior of Citric Acid Complexes with Cu²⁺ and Zn²⁺ in Heterobimetallic Complexes - Eissa Mohamed Almbrok; Hassana Abdelkader; Adda Mohamed (African Journal of Advanced Pure and Applied Sciences, 2025)
This study investigates the influence of pH on the coordination behavior of citric acid with Cu²⁺ and Zn²⁺ ions in aqueous solution using potentiometric method. Experiments were performed at 25 °C and constant ionic strength (0.1 M KCl) to determine protonation constants and stability constants (log β) of binary and heterobimetallic complexes. The results showed three dissociation steps for citric acid (pKa = 3.2, 4.6, 5.6), with partially deprotonated species (H₂Cit⁻, HCit²⁻) being the most active in metal binding between pH 3–6. Copper formed more stable complexes (log β ≈ 9.5) than zinc (log β ≈ 7.5), while the mixed Cu–Zn system exhibited enhanced stability (log β ≈ 14) due to synergistic coordination. Increasing ionic strength reduced complex stability, consistent with the Davies model. Spectroscopic data confirmed the formation of stable Cu²⁺–citrate and Zn²⁺–citrate species. Overall, the findings highlight strong pH-dependent complexation and cooperative metal–ligand interactions relevant to bioinorganic and environmental systems.